Synergy and medial effects of multimodal cueing with auditory and electrostatic force stimuli on visual field guidance in 360° VR - Sawahata, Yasuhito; Harasawa, Masamitsu; Komine, Kazuteru (Frontiers in Virtual Reality, 2024)
This study investigates the effects of multimodal cues on visual field guidance in 360° virtual reality (VR). Although this technology provides highly immersive visual experiences through spontaneous viewing, this capability can disrupt the quality of experience and cause users to miss important objects or scenes. Multimodal cueing using non-visual stimuli to guide the users' heading, or their visual field, has the potential to preserve the spontaneous viewing experience without interfering with the original content. In this study, we present a visual field guidance method that imparts auditory and haptic stimulations using an artificial electrostatic force that can induce a subtle "fluffy" sensation on the skin. We conducted a visual search experiment in VR, wherein the participants attempted to find visual target stimuli both with and without multimodal cues, to investigate the behavioral characteristics produced by the guidance method. The results showed that the cues aided the participants in locating the target stimuli. However, the performance with simultaneous auditory and electrostatic cues was situated between those obtained when each cue was presented individually (medial effect), and no improvement was observed even when multiple cue stimuli pointed to the same target. In addition, a simulation analysis showed that this intermediate performance can be explained by the integrated perception model; that is, it is caused by an imbalanced perceptual uncertainty in each sensory cue for orienting to the correct view direction.The simulation analysis also showed that an improved performance (synergy effect) can be observed depending on the balance of the uncertainty, suggesting that a relative amount of uncertainty for each cue determines the performance. These results suggest that electrostatic force can be used to guide 360° viewing in VR, and that the performance of visual field guidance can be improved by introducing multimodal cues, the uncertainty of which is modulated to be less than or comparable to that of other cues. Our findings on the conditions that modulate multimodal cueing effects contribute to maximizing the quality of spontaneous 360° viewing experiences with multimodal guidance.